Some Insights on English Studies in Indonesia - Nugroho, Ridwan Arif (Ahmad Dahlan Journal of English Studies, 2014)
AbstractThe paper tries to offer some insights on English language studies in Indonesian universities. It seems that we need to reconsider the position of English studies in Indonesia. It is high time to respond to the need to prepare our students to realize there are many Englishes. For many decades, we have been focusing our attention to the West (British and American English) while the fact shows that English is no longer singular. Thus, focusing our attention to the West is not a wise choice. English departments in Indonesia should serve the interest of the students studying there.